HUBUNGAN POLA ASUH MAKAN DENGAN STATUS GIZI PADA BALITA - Romaito Togatorop, Cyntia; Sinurat, Suryati; Rajagukguk, Marlina (Jurnal Kedokteran Methodist, 2022)
Background: The impact of food and the use of nutrients consumed by a person that affects the state of a person’s body is called nutritional status. Nutritional status is divided into several indicators. In 2017, UNICEF stated that there were 51 million (7.5%) under-fives experiencing wasting, 151 million (22%) under-fives experiencing stunting and 92 million (13.5%) under-fives in the world. Method : The research was conducted using a literature study or literature review method that focuses on the results of writing related to the tittle through searching accredited journal sites such as Google Schoolar, Google, and Pubmed, in the period 2017 -2021. Conclusion: Based on the research that has been done there is a relationship between eating parenting and nutritional status in toddlers.